Micro-CT evaluation of root canal preparation with rotary instrumentation on prototyped primary incisors - Rafael dos Reis MORAES; Renata PEREZ; Aline Saddock Sá da SILVA; Alessandra Silveira MACHADO; Ricardo Tadeu LOPES; Andréa Vaz Braga PINTOR; Laura Guimarães PRIMO; Aline de Almeida NEVES (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract This study aimed to evaluate the endodontic instrumentation outcomes with asymmetrical files compared to reciprocating and hand files (HFs) in 3D-printed prototypes of upper primary incisors using micro-computed tomography (micro-CT). For this purpose, 50 prototypes were randomly divided (n = 10) according to the instrumentation technique as follows: HFs, a reciprocating file (WaveOne® Gold [WOG]), and three asymmetrical movement files: XP-Endo® Shaper (XPS), XP-Endo® Finisher (XPF), and XP Clean (XPC). The specimens were scanned and, after registration of the baseline and instrumented volumes, changes in the root canal volume (RCV), debris accumulation, removed root material volume (RRMV), non-instrumented areas, and the presence of cracks/perforations were quantified. Data were analyzed by analysis of variance and Student's t-test, while the effect size was calculated for statistically significant outcomes. All groups showed an increase in RCV after instrumentation (p < 0.05), but this was higher with HFs (p < 0.05). Accumulated debris was higher for WOG and XPS (p < 0.05), but WOG exhibited more in the medium and apical third areas. HFs showed the highest RRMV (p < 0.05), especially at the apical third. The non-instrumented areas were lower for HFs and XPC than for the other systems (p < 0.05). Cracks were present in a few WOG (n = 2) and HF specimens (n = 3) and in this group, one of the cracked specimens and two others showed perforations. The asymmetric systems resulted in conservative dentin removal and fewer cracks/perforations as compared to HFs and a reciprocation file in prototyped primary upper incisors. XPC showed the best compromise between RRMV and non-instrumented areas with a low accumulation of debris.